Pengaruh Pemasaran Digital terhadap Keputusan Pembelian pada Richeese Factory Kisamaun, Tangerang - Fajar Nurcahyo; Ronald Tehupuring; Puri Swastika Gusti Krisna Dewi; Andreas Bramantyo; Yulia Krismael Lembu; Yohana Deo Utami Silaban; Utari Srilestari; Akhmad Fauzan (Universitas Yatsi Madani, 2025)
The advancement of digital technology has significantly transformed marketing strategies, particularly within the culinary industry. This study aims to analyze the impact of digital marketing on purchasing decisions at Richeese Factory in Kisamaun, Tangerang, using a quantitative approach through a survey involving 111 respondents selected through purposive sampling. The data were analyzed using the Structural Equation Modeling (SEM) method, with the assistance of SmartPLS version 4 software. The findings indicate that digital marketing has a positive and significant influence on purchasing decisions. Several key indicators contribute to this effect, including information accessibility, customer interactivity, the credibility of marketing content, and the effectiveness of social media in enhancing brand awareness and consumer purchase interest. The study concludes that a well-designed digital marketing strategy can significantly improve consumer purchasing decisions. Therefore, Richeese Factory is encouraged to continue optimizing its digital marketing efforts through social media and e-commerce platforms to strengthen its competitiveness and increase customer loyalty.